Analysis of the frequency of maxillary sinus pathology among male and female adults - M. Cherkes; V. Student; Z. Masna; K. Ivasivka; Kh. Rudnytska (Journal of Education, Health and Sport, 2021)
The maxillary sinuses diseases are an actual clinical problem today. The aim of our study was to determine the frequency of pathology of the maxillary sinuses of different origin and its age dynamics in adults.